Baby from another lady: Regulating surrogacy in the Philippines - Syjuco, Leonard Martin E. (Animo Repository, 2015)
When science was not yet as advanced as now, childless couples had only one option in order to have their own child: to adopt. The emergence of the concept of surrogacy gave hope to childless couples to have their own baby. However, in recent years, there are cases which show that surrogacy may cause serious problem situations. This thesis studies the laws of the countries which allow, disallow and regulate surrogacy. Furthermore, this thesis studied the concept of surrogacy in relation to the laws of the Philippines. As a result, there are laws, such as the Constitution, the Civil Code of the Philippines and some special laws which are violated by the concept of surrogacy. As such, surrogacy should be banned, proscribed and prohibited in the Philippines. A bill is proposed to ban and proscribe all types and all kinds of surrogacy in the Philippines